Kedudukan Wanita Bali yang Daha Tua (Tidak Menikah) terhadap Hak Warisan di Desa Adat Abianbase Kabupaten Gianyar - Anak Agung Galuh Ratna Chyntia Dewi; I Wayan Wesna Astara; I Ketut Sukadana (Warmadewa Press, 2020)
Balinese unmarried women still do not get legal protection in the rights of inheritance. This is because the Hindu community in Bali adheres to the Patrilinial family system that only men are entitled to receive inheritance. In the development of the main assembly of Pakraman village, Bali (MUDP) has taken the initiative to grant the rights of inheritance to women with their parents' property. From the fact, then the research problems are formulated as (1) How the position of unmarried Balinese women in the customary village of Abianbase? (2) How to implement the birthright of unmarried Bali women in the customary village of Abianbase. The research method used is empirical-juridical research implemented by researching the reality in Abianbase customary village and the Supreme Pasamuhan Decree of MUDP III. The data types used are the primary data and the secondary data. Finally it was concluded that the position of unmarried women equals the women’s position on the customary law of Bali. The unmarried woman cannot have a birthright except the right to take advantages of their parents’ inheritance as the cost of living with other heirs. The implementation is, in the traditional village Abianbase after the decree of the main assembly of Pakraman village about the results of Pasamuhan Agung III MUDP Bali, there’ a need for a relatively longer time because it concerns the tradition that has been ingrained in society life.